2022
DOI: 10.1007/s11605-022-05248-6
|View full text |Cite|
|
Sign up to set email alerts
|

Risks and Prevention of Surgical Site Infection After Hernia Mesh Repair and the Predictive Utility of ACS-NSQIP

Abstract: Aim The aim of this paper was to provide a narrative review of surgical site infection after hernia surgery and the influence of perioperative preventative interventions. Methods The review was based on current national and international guidelines and a literature search. Results Mesh infection is a highly morbid complication after hernia surgery, and is associated with hospital re-admission, increased health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 84 publications
(162 reference statements)
1
22
0
3
Order By: Relevance
“…SSI was most commonly seen in those with increased BMI and incisional hernia. Previous work has demonstrated the association of these factors with subsequent SSI 13 , 14 . While these factors, along with diabetes mellitus and smoking status are preferably optimized in the elective setting, there is no meaningful opportunity to mitigate these risks in the acute setting.…”
Section: Discussionmentioning
confidence: 96%
“…SSI was most commonly seen in those with increased BMI and incisional hernia. Previous work has demonstrated the association of these factors with subsequent SSI 13 , 14 . While these factors, along with diabetes mellitus and smoking status are preferably optimized in the elective setting, there is no meaningful opportunity to mitigate these risks in the acute setting.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, smoking had been shown to be a modifiable risk factor for complications following hernia repair. 10 , 18 There were two patients who together cumulated 6 of the 14 total complications. Both of these patients had morbid obesity (a BMI of ≥ 40), which also has been shown to be a modifiable risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent procedures were excluded because a mesh is not placed due to the high risk for harboring infection. 10 Additionally, not placing a mesh had been shown to have higher hernia recurrence rates.…”
Section: Methodsmentioning
confidence: 99%
“…По данным современных авторов, риск развития последних закономерно возрастает с повышением объема и сложности вмешательства, определяемого размерами грыжевого дефекта и характеристиками клинического случая, включая класс зоны операции согласно классификации US Centers for Disease Control and Prevention [9]. Достоверными факторами риска инфекции эндопротеза являются класс пациента III и более по классификации American Society of Anesthesiologists, пожилой возраст, курение, хроническая обструктивная болезнь легких, морбидное ожирение, предшествующие инфекции в зоне вмешательства, продолжительность операции, непреднамеренная энтероили колотомия, наличие свищей [10,11,12]. Вмешательства на кишечнике одновременно с протезирующей пластикой сопровождаются достоверно худшими результатами [13,14].…”
unclassified
“…Известно также о влиянии на риск иммунодепрессивных препаратов, глюкокортикостероидов, сахарного диабета и ряда других коморбидных заболеваний [11][12][13][14][15]. Экстренный характер вмешательства, открытый доступ по сравнению с лапароскопическим также являются факторами риска [11,13,16].…”
unclassified